Evaluation of Correlation of Blood Type, Gender, Age and BMI on Cognitive Ability of 125 top 10 Undergraduated Students - Shamalwal, Sayed Rahim Shah; Amal, Maghferatullah; Gul Sharif, Sherzad (Journal for Research in Applied Sciences and Biotechnology, 2023)
Introduction: Cognitive abilities have been the focus of behavior investigations for decades. Cognitive impairment share many common risk factors, such as hypertension, elevated cholesterol, hyperglycemia, and obesity are all associated with longitudinal declines in cognitive function and dementia. We investigated correlation of blood type, age, gender and BMI on cognitive abilities of 125 top 10 undergraduated medical students. Objective: This study aimed to determine and evaluate the correlation of blood type, age, gender and BMI on cognitive abilities of 125 top 10 undergraduated medical students in Ahmad Shah Abdali Higher Education Institute of Khost province of Afghanistan. Method and Materials: It is prospective descriptive cross sectional study, on 125 top 10 undergraduated medical students in Ahmad Shah Abdali Higher Education Institute of Khost province from 2019/ Nov / 07 to 2020/ Apr / 06. The including parameters were blood type, age, gender, BMI of all 125 participants under study that recorded in computer special format. Blood type and BMI are done by special regents and scale. Recorded findings processing, comparison and evaluation results have been identified by IBM SPSS-25 version. Results: The study was conducted during (5) month on 125 top 10 undergraduated medical students in Ahmad shah Abdali Higher Education Institute of Khost province. Initially we described all participants according to gender and age. At the current study the female participants were 71 (56.8) and male were 54 (43.2), with (mean age: 21.27 ± 2.38; range: 17-29 years). All participants of this study were from all classes (1st, 2nd, 3rd, 4th and 5th) and each main class has two or more subclasses. Statistic description of all participants, according to blood type shows that (B+) blood type was more prevalent 38 (30.4) among the whole participants, and in the second grade was (O+) blood type 28 (22.4). For comparison we divided all participants into two groups, high cognitive group according to roll number (from 1 to 5, roll number one is the best learned and intelligent student in the class and this grade is gradually decreased up to roll number 10th) and low cognitive group according to roll number (from 6 to 10). In the high cognitive group included 64 students. Statistic description of the high cognitive group shows that number of female 36 (56.3) participants is more prevalent than male 28 (43.8) participants. The (B+) blood type participants are more prevalent 25 (39.1) inside this group, and the (O+) blood type 14 (21.9) is in the second grade. Mean age: 21.18 ± 2.20; range: 17-28 years. Mean BMI; 22.84± 3.43, range: 16.48-31.14. In the low cognitive group included 61 students. Statistic description of the low cognitive group shows that prevalent of female 35 (57.4) higher than male 26 (42.6). The prevalent of (A+) blood type participants were highest 16 (26.2) inside this group, and the (O+) blood type 14 (23.0) is in the second grade. Mean age: 21.36 ± 2.57; range: 17-29 years. Mean BMI; 23.11± 3.31, range: 16.42-30.10. For comparison between high and low groups we detected following findings. The number of female in high cognitive group was more prevalent 36 (28.8) than female in low cognitive group 35 (26.85), (P<1.00). The (B+) blood type was more prevalent in high cognitive group 25 (20.0), and the second grade (O+) blood type 14 (11.2) and the third grade (A+) blood type are gradually decreased, but in comparison to the blood type in low cognitive group (A+) blood type is more prevalent 16 (12.28) than the others, and the second grade was (O+) blood type 14 (10.74), (P<0.390). Mean average and age range are in the high group: 21.18 ± 2.20; range: 17-28 years, but in low group mean average and age range: 21.3607 ± 2.57; range: 17-29 years. Mean average and BMI range in the high group is; 22.84 ± 3.43, range: 16.48-31.14, but in low group are 23.11 ± 3.31, range: 16.42-30.10, (P<0.735). Conclusion: Overall, findings of our study indicated that, age, gender, blood type and BMI have no significant correlation with cognitive ability of undergraduated students. However, this issue needs to further investigations in socialeconomical, cultural, political, genetics, environment and geographical areas to confirm these findings.